Large-scale vertical graphene on nickel foil as a binder-free electrode for high performance battery-like supercapacitor with an aqueous redox electrolyte - Xiaobo Chen; Yipei Li; Mingliang He; Binghua Zhou; Deliang Cheng; Shien Guo; Keng Xu; Cailei Yuan; Mingxi Wang; Hironori Ogata; Gan, Melvin Jet Hong; Yoong Ahm Kim; et al. (Elsevier B.V., 2023)
Due to the special three-dimensional structures and excellent physicochemical properties, vertical graphene (VG) has been extensively investigated as potential material for supercapacitors. However, achieving VG-based supercapacitors with high-energy density and high-power density is a still tremendous challenge. Here we attempt to synthesize large-scale VG films on flexible substrates and design a novel battery-like supercapacitor (BSCs) with the VG on Ni foil (VG@Ni) as a binder-free electrode operating in the KOH electrolyte with the redox additives of K₃Fe(CN)₆ and/or K₄Fe(CN)₆. The VG@Ni electrodes demonstrate an ultrahigh areal capacitance of 1453 mF cm⁻² at 5 mA cm⁻² in 1 M KOH electrolyte with adding 0.07 M K₃Fe(CN)₆ and 0.07 M K4Fe(CN)6, coulombic efficiency greater than 90%, and long-life cycling stability (capacitance retention is 99.3% after 20000 charge-discharge cycles). The BSCs, which are assembled with two identical VG@Ni electrodes, deliver the areal capacitance of 231 mF cm⁻² with energy density of 32 μWh cm⁻² and power density of 2498 μW cm⁻² at 1 mA cm⁻². These outstanding performances can be ascribed to the special feature and excellent properties of VG materials, high electronic conductivity of binder-free VG@Ni electrode, faradaic properties of redox electrolyte, and synergistic effects between the VG film and redox electrolyte.